2010
DOI: 10.1002/pi.2966
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel siloxane‐imide‐containing polybenzoxazine

Abstract: A novel siloxane-imide-containing polybenzoxazine based on N,N -bis(N-phenyl-3,4-dihydro-2H-benzo[1,3]oxazine)-5, 5 -bis(1,1 ,3,3 -tetramethyldisiloxane-1,3-diyl)-bis(norborane-2,3-dicarboximide) (BZ-A1) was successfully synthesized. The thermal properties of BZ-A1 are superior to those of conventional polybenzoxazines lacking siloxane groups. Polymerized BZ-A1 possesses extremely low surface free energy (γ s = 15.1 mJ m −2 ) after curing at 230 • C for 1 h. Moreover, the surface free energy of polymerized BZ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The curing parameters derived from ( Figure 6) are compiled in (Table 1). The BAB [18] starts to cure at 163°C and ends at 304°C, with the cure maximum at 229°C. And the associated heat of enthalpy of cure reaction for BAB is 273 J/g.…”
Section: Dsc Studies: Curing Behavior Of Benzoxazines and Glass Transmentioning
confidence: 99%
See 1 more Smart Citation
“…The curing parameters derived from ( Figure 6) are compiled in (Table 1). The BAB [18] starts to cure at 163°C and ends at 304°C, with the cure maximum at 229°C. And the associated heat of enthalpy of cure reaction for BAB is 273 J/g.…”
Section: Dsc Studies: Curing Behavior Of Benzoxazines and Glass Transmentioning
confidence: 99%
“…[10,17] Recently, lot of work is being done in the field of polybenzoxazine. Chen et al [18] studied polybenzoxazines containing siloxane and imide group. Santhosh Kumar et al [19] studied polybenzoxazines containing different cyclohexyl moieties and reported that the char yield is proportional to the aromatic content of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, introducing the sulfone moiety into benzoxazine can enhance the rigidity, modulus and thermal stability of the corresponding cured resins . Another important way of enhancing the performance is to fabricate inorganic − organic hybrids of polybenzoxazine with polysiloxane, which could improve its flexibility, thermal stability (in terms of initial decomposition temperature and char/ceramic yields) and flame retardancy and increase its glass transition temperature . Moreover, the hydrogen bonds formed in the benzoxazine ring‐opening process favour the arrangements of organic fragments of the polysilsesquioxanes .…”
Section: Introductionmentioning
confidence: 99%
“…In practice, many researchers incorporate flexible SiOSi linkages into benzoxazine molecules to improve the processability and brittleness of polybenzoxazines, and various siloxane‐containing benzoxazines were synthesized from 1,3‐bis(3‐aminopropyl)tetramethyldisiloxane, 3‐aminopropyltriethoxysilane, α,ω‐bis(aminopropyl)polydimethylsiloxane, siloxane‐containing dihydroxyl compounds, and γ‐aminopropyldimethoxy‐methylsilane and dimethyldiethoxysilane, or from hydrosilylation reaction of allyl‐containing benzoxazines with 1,1,3,3‐tetramethyldisiloxane and hydride terminated polydimethylsiloxane . These works incorporated different siloxanes into benzoxazines, which enhance the properties of the resultant polybenzoxazines, such as glass transition temperature ( T g ) and toughness, thermal stability, flame retardancy, surface hydrophobicity, elongation at break, and flexibility, but they did not involve the research on SME for polybenzoxazines.…”
Section: Introductionmentioning
confidence: 99%